Mild dehydration in dyspeptic athletes is able to increase gastrointestinal symptoms: Protective effects of an appropriate hydration. Issue 1 (16th December 2018) - Zito, Francesco Paolo; Gala, Antonietta; Genovese, Daniela; Vozzella, Letizia; Polese, Barbara; Cassarano, Sara; Cargiolli, Martina; Andreozzi, Paolo; Gelzo, Monica; Sarnelli, Giovanni; Frisso, Giulia; Cuomo, Rosario
Abstract: Background: Water balance influences gastrointestinal (GI) activity. Our aim was to evaluate how dehydration and rehydration with different types of water are able to affect GI activity in healthy and dyspeptic athletes. Methods: Twenty non‐competitive athletes, respectively 10 healthy and 10 dyspeptic subjects, were enrolled. All subjects underwent three test sessions (0, A, B) of 6 hours. Dehydration was achieved with a walking/jogging exercise test on a treadmill. After exercising, 500 mL of calcium‐bicarbonate (Test A) or soft water (Test B) were administered, while no rehydration was provided during Test 0; thereafter, all subjects consumed a light lunch. GI symptoms were evaluated during each test and an electrocardiogram (ECG) Holter recording was performed at the end of the exercise. Key Results: Dyspeptic subjects exhibited higher overall symptoms during Test 0 (VAS: 30.8 ± 0.8 mm) compared to Test A (18.4 ± 1.1, P  < 0.001) and Test B (24.4 ± 1.3, P  < 0.001). However, analyzing GI symptoms, only subjects receiving calcium‐bicarbonate water (Test A) showed significantly lower symptomatic scores compared to Test 0 or Test B. Moreover, heart rate variability analyses revealed that only in Test A dyspeptic patients exhibit a trend to a decrease in the post‐prandial low/high frequency (LF/HF) ratio, similarly to healthy subjects, while in Test 0 and Test B, post‐prandial LF/HF ratio was increased compared to the pre‐prandial phase. Conclusions and Inferences: Our results show that mild dehydration in dyspeptic athletes is able to increase GI symptoms but an adequate rehydration, with calcium‐bicarbonate water, is able to improve post‐exercise disturbances restoring sympathovagal imbalance. Abstract : Hydration status may influence symptoms onset and severity in dyspeptic patients. However, different types of water may differently affect gastrointestinal activity since calcium‐bicarbonate water seems to improve dyspeptic symptoms, induced by physical stress.